2000
DOI: 10.1128/jb.182.17.4998-5000.2000
|View full text |Cite
|
Sign up to set email alerts
|

Plasmid pGS5 from the Hyperthermophilic Archaeon Archaeoglobus profundus Is Negatively Supercoiled

Abstract: We present evidence that, in contrast to plasmids from other hyperthermophilic archaea, which are in the relaxed to positively supercoiled state, plasmid pGS5 (2.8 kb) from Archaeoglobus profundus is negatively supercoiled. This might be due to the presence of a gyrase introducing negative supercoils, since gyrase genes are present in the genome of its close relative A. fulgidus, and suggests that gyrase activity predominates over reverse gyrase whenever the two topoisomerases coexist in cells.Previous topolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
26
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 16 publications
1
26
0
Order By: Relevance
“…Nevertheless, similar to pTP1, pTP2 is likely to replicate using the RC mechanism. ORF3 of pTP2 encodes a putative protein (RepTP2) of 252 aa which shares significant sequence similarity with RCReps encoded by diverse archaeal MGE (Table 2), including Archaeoglobus profundus plasmid pGS5 (24), putative Methanococcus voltae A3 provirus (MVV) (46), and a group of pleomorphic haloarchaeal viruses (47). Sequence analysis of RepTP2 showed that, unlike RepTP1, it possesses two conserved Tyr resi- dues in motif 3 ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, similar to pTP1, pTP2 is likely to replicate using the RC mechanism. ORF3 of pTP2 encodes a putative protein (RepTP2) of 252 aa which shares significant sequence similarity with RCReps encoded by diverse archaeal MGE (Table 2), including Archaeoglobus profundus plasmid pGS5 (24), putative Methanococcus voltae A3 provirus (MVV) (46), and a group of pleomorphic haloarchaeal viruses (47). Sequence analysis of RepTP2 showed that, unlike RepTP1, it possesses two conserved Tyr resi- dues in motif 3 ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In this phylum, plasmids have been isolated from hyperthermophilic organisms belonging to three different orders, the Methanococcales (genus Methanocaldococcus) (23), Archaeo-globales (24), and Thermococcales (25). However, viruses have been isolated only from members of the latter order (26,27).…”
mentioning
confidence: 99%
“…Finally, module 10 includes two small rolling-circle plasmids, Archaeoglobus profundus plasmid pGS5 (71) and Thermococcus prieurii plasmid pTP2 (72), which connect to members of the genus Alphapleolipovirus (Halorubrum pleomorphic viruses 1, 2, and 6) through an RCRE. The latter protein is also shared with the putative provirus MVV, which is related to Turriviridae from module 6, as well as with the Sulfolobus monocaudavirus 2 (SMV2) from module 9.…”
Section: Figmentioning
confidence: 99%
“…It has not been established precisely how this enzyme can protect against DNA thermal instability. DNA positive supercoiling per se may not be the direct cause, because supercoiling in hyperthermophiles is highly variable ranging from positively supercoiled to relaxed or even negatively supercoiled (11). The biochemical activity of reverse gyrase as a renaturase for single-stranded DNA may have a critical role in maintaining genome stability at high temperature (12).…”
mentioning
confidence: 99%